Importance of S-point in the Management of Severe Epistaxis - M. Al-Ani , Raid (AL-Kindy College Medical Journal, 2023)
Although severe epistaxis is uncommon, it is serious. The systematic endoscopic nasal examination is an essential step in identifying the bleeding point and aiding electrocauterization. Currently, the S-point, which is located in the superior part of the nasal septum behind the septal body and corresponding to the axilla of the middle concha, is identified in about 30% of cases with severe epistaxis. Cauterization of this point has an excellent rate of controlling the bleeding and preventing its recurrence. We aimed to highlight the significance of the S-point in the management of severe cases of epistaxis.